Blanca Sol - Cabello de Carbonera, Mercedes (Vervuert Verlagsgesellschaft, 2004)
Cabello de Carbonera inicia con esta novela el realismo social en la literatura peruana
Description based on online resource; title from PDF title page (publisher's Web site, viewed 26. Mrz 2019)
Keywords: Hispanic Literature, general; Literary Studies; LITERARY CRITICISM / American / General